2023
DOI: 10.1007/s11764-023-01426-w
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor rs6265 polymorphism is associated with severe cancer-related fatigue and neuropathic pain in female cancer survivors

Taichi Goto,
Diane Von Ah,
Xiaobai Li
et al.

Abstract: Purpose This study examined the relationships between a single-nucleotide polymorphism (SNP) of brain-derived neurotrophic factor (BDNF) rs6265 and psychoneurological (PN) symptoms in female cancer survivors. Methods This secondary analysis examined 393 study participants. In addition to demographic variables, self-reported PN symptom scores (anxiety, bodily pain, depression, fatigue, neuropathic pain, and sleep disturbance) were collected using the Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The recruitment methods and eligibility criteria of the parent study are described in our previous paper. 24 Briefly, we enrolled BCS if they were ≥21 years old, were at ≥6 months after completing adjuvant/neo‐adjuvant therapies for breast or colorectal cancer (current Aromatase Inhibitors or Tamoxifen use at the time of enrollment was allowed), and had self‐reported CRCI. In this analysis, only female BCS with early‐stage BC (I–III) were included.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The recruitment methods and eligibility criteria of the parent study are described in our previous paper. 24 Briefly, we enrolled BCS if they were ≥21 years old, were at ≥6 months after completing adjuvant/neo‐adjuvant therapies for breast or colorectal cancer (current Aromatase Inhibitors or Tamoxifen use at the time of enrollment was allowed), and had self‐reported CRCI. In this analysis, only female BCS with early‐stage BC (I–III) were included.…”
Section: Methodsmentioning
confidence: 99%
“…Participant characteristics, including demographic information and medical/treatment information, were obtained using an investigator‐initiated sociodemographic form. 24 The version 1.0, 8‐item short‐forms of the Patient‐Reported Outcomes Measurement Information System (PROMIS) ® Cognitive Abilities and Cognitive Concerns subscales assessed perceived CRCI. 25 The Cognitive Abilities subscales assessed CRCI by responding to statements like, “My memory has been as good as usual” and “I have been able to concentrate.” Higher scores indicate higher cognitive ability.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, research has established a connection between individuals carrying the Val allele and an increased susceptibility to chronic postsurgical pain [138], as well as a correlation with the severity of depression [139]. In addition, a recent clinical study in cancer survivors revealed that those with the Met/Met genotype of BDNF rs6265 reported significantly more severe cancer-related neuropathic pain and fatigue than those with other genotypes [140].…”
Section: Genetics and Bdnf In Chronic Painmentioning
confidence: 99%